Dentofacial Deformities and Implications on Quality of Life: A Presurgical Multifactorial Analysis in Patients Seeking Orthognathic Surgical Treatment - Paula Gomes, Adrielle Mendes de [UNESP]; Garbin, Cléa Adas Saliba [UNESP]; Silva Ferraz, Flavio Wellington da [UNESP]; Saliba, Tânia Adas [UNESP]; Garbin, Artênio José Isper [UNESP] (Elsevier B.V., 2019)
Purpose: The purpose was to perform a quality-of-life survey in patients with skeletal malocclusion before undergoing orthognathic surgery, as well as delineate the sociodemographic profile and detect factors that may alter the quality of life. Patients and Methods: This cross-sectional study was carried out in patients who sought care at the Hospital das Clinicas of the University of Sao Paulo Medical School (N = 106; average age, 27.2 years). Participants answered the Oral Health Impact Profile 14 (OHIP-14) questionnaire and Orthognathic Quality of Life Questionnaire (OQLQ). The chi(2 )or Fisher test was used to verify the association between impact and sociodemographic variables. Results: On the Oral Health Impact Profile 14 (OHIP-14) questionnaire, the 'psychological incapacity dimension (64.15%) presented a higher prevalence of impact. The marital status of the interviewees had a statistically significant effect on the impact of quality of life (P = .0119). On the Orthognathic Quality of Life Questionnaire (OQLQ), the facial esthetics dimension represented 81.13% in the prevalence of impact on quality of life. The 'gender variable had a statistically significant effect on the quality of life of the respondents (P = .0005), with women having an 11.78 times greater chance of having this impact. Conclusions: In this study, psychological factors and esthetics exerted a strong influence on the quality of life of patients with dentofacial deformities, overlapping with functional aspects. (C) 2018 American Association of Oral and Maxillofacial Surgeons